The Role of fact-checking sites during the Israel-Palestine conflict - Reza, Raiyan; Sunvy, Ahmed Shafkat (The Indonesian Journal of Communication Studies, 2023)
As a result of the information explosion, a great amount of data has been created, including stuff that is deceptive, ethically problematic, tolerant, and hateful. The rapid and extensive circulation of false news, on the other hand, appears to show that many people either do not comprehend the concept of "fake news" or, if they do, share it nonetheless. False news has increased in Palestine in concert with the expansion of social media, maybe more than in other countries due to the ongoing Israeli occupation and the broader Arab-Israeli conflict. This research studied 147 news items from three important fact-checking websites—AP Fact Check, Reuters Fact Check, and AFP Fact Check—to detect trends in misinformation on the Israeli-Palestinian conflict. The results are going to help in understanding the influence of media coverage on peace initiatives and conflict settlement, and they have significant implications for the study of interpersonal disputes, past recollections, and political inaccuracies.